Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi, Kemajuan Teknologi Terhadap Penerapan Akuntansi SAK EMKM pada UMKM Batik di Kota Surakarta - Salahudin Alayubi; Eko Triyanto (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2022)
MSMEs are currently a sector that is expected to contribute to recovering the economic recession due to the Covid-19 pandemic. The Surakarta city government explores the potential of batik, in an effort to create superior products that can boost the local and regional economy. The Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) is a simplification of the previous financial accounting standards, namely the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) in an effort to improve the accounting application of SAK EMKM. The purpose of this study was to analyze the effect of education level, accounting understanding, technological advances on the application of SAK EMKM accounting on Batik SMEs in Surakarta City. The research was conducted in Surakarta City with a sample of 57 batik MSME managers/entrepreneurs from 138 Batik MSME entrepreneurs in the city of Surakarta. The sampling technique used incidental sampling, the data sources were obtained from research questionnaires with a Likert scale, data analysis techniques used instrument tests (validity and reliability), classical assumption tests (normality, multicollinearity and heteroscedasticity), multiple linear regression tests and hypothesis testing. The results of the study show that the level of education, understanding of accounting, technological progress partially or simultaneously influences the application of SAK EMKM accounting on Batik MSMEs in Surakarta City.